Soil pollution: Processes and dynamics - Yaron, Bruno (Springer-Verlag, 1996)
This book is delicated to understanding the processes governing the fate of pollutants, originating from both agriculture and industry, in soils. Investigated here are the properties of the interacting materials, pollutant partitioning between the soil phases, pollutant behaviour in soils affected by environmental factors